Century of warfare II the history of the United States at war in the 20th Century ([S.l.] : Wayang Tinggi Corporation (distributor), 2009)
The story about US in faced big wars, World War II and the Korean War. Tho World War II, details how the tide is fully turned and the Axis is driven back, Europe is invaded, Germany defeated and Japan stands alone, defiant. The Korean War, the situation was stabilized and following a brilliant offensive, the communist armies were thrown back, only to surge forward again with Chinese support. This is the story of the see-saw fighting on the Korean Peninsula that ended in an uneasy peace almost fifty years ago
Title from container
DVD Format
Subtitles in Malay, English and Chinese
Keywords: World War, 1939-1945 -- United States; Korean War, 1950-1953 -- United States